A systematic review of the correlates and management of nonpremature ejaculatory dysfunction in heterosexual men - Raouf Seyam (Therapeutic Advances in Urology, 2013)
Introduction: A better understanding of ejaculatory disorders has led to an increasing interest in nonpremature ejaculatory dysfunction (non-PE EjD). Current reviews on the subject use a symptom-based classification to describe ejaculatory dysfunction even when it is a single case report. While these reviews provide important information on the disorder, a clearer picture of the prevalence of non-PE EjD in relation to the community and various pathophysiologic states is needed. Objectives: The objective of this study was to provide a systematic review of studies of non-PE EjD excluding single case reports. Methods: A systematic review of Medline for terms including ejaculation, orgasm or hematospermia. Association with terms delay, pain or headache was made. The search was restricted to male gender and articles written in English. Abstracts were reviewed and those mainly concerned with premature ejaculation were excluded. Results: A total of 333 articles on non-PE EjD were identified. The condition was reported in community-based studies. In certain patient populations, non-PE EjD was commonly reported in association with antidepressant and antipsychotic treatments, in patients with chronic prostatitis/chronic pelvic pain syndrome, patients with lower urinary tract symptoms particularly in association with medical or surgical treatment, patients with retroperitoneal surgery and in patients with neurological diseases. Few articles were concerned with treatment options. Conclusion: There is a significant prevalence of non-PE EjD in the community and in association with particular disease states or as a side effect of medical or surgical interventions. There is a need to direct efforts to prevent and treat these conditions.